Cost‐Efficient Aluminum Open‐Cell Foams: Manufacture, Characterization, and Heat Transfer Measurements. Issue 8 (26th April 2018) - Monno, Michele; Negri, Daniela; Mussi, Valerio; Aghaei, Pedram; Groppi, Gianpiero; Tronconi, Enrico; Strano, Matteo
Abstract : Metal foams may have applications in the field of catalytic supports, but the available manufacturing processes are too expensive for industrial use. The goal of the paper is to investigate and compare alternative cost‐efficient manufacturing methods, aimed at producing open‐cell aluminum foams for low‐temperature catalytic applications. The explored process chains are 1) solid state bonding of stacked thin slices of closed cell foams; 2) the conventional method of sintering and dissolution of aluminum powders with space holder; 3) sintering and dissolution of recycled aluminum turning chips with space holder. The process chains and their main parameters are described in detail. The morphological properties of the produced open‐cell foam samples, relevant to catalytic applications (cell size, hydraulic porosity, total porosity, surface to volume ratio), are measured and compared. Finally, their heat transfer properties are experimentally compared. The foams produced by the sintering and dissolution process exhibit the most favorable compromise among the goals of reducing the manufacturing cost, increasing the heat transfer coefficients, controlling the cell morphology. Abstract : Three manufacturing process chains are compared, aimed at producing cost‐efficient open cell metal foams for potential catalytic applications. The three foam types are: 1) obtained by sintering and dissolution of pressed aluminium powder, 2) obtained by sintering and dissolution of pressed recycled lathe turning aluminium chips, 3) obtained by diffusion bonding of thin slices of closed cell aluminium foam. Foam type A proved to be the best compromise in terms of hydraulic porosity, surface‐to‐volume ratio, and estimated production cost. Their heat transfer properties have been tested in an experimental rig with a heated gas flow, with promising results.